Blending Construction In English Foods And Beverages In Indonesia: Linguistics And Cultural Views - Sulhizah Wulan Sari; Rini Martiwi (Wanastra: Jurnal Bahasa dan Sastra, 2020)
This research aims at investigating the composing of the portmanteau word in food and beverage names or brands in Indonesia referring to the types of blending in the source word proposed by John Algeo. Based on the linguistic and cultural view, the fact shows the name or brand of foods and beverages carry their characteristics, identities, and motives in its usage. The descriptive qualitative method is applied in this study by collecting the English food and beverage name or brand taken from offline and online searching. Offline data is searched by the observation in Mall, shop, and restaurant. Online data is gained from the internet web starting from March up to May. The collected data from online and offline is tabulated all together into types of blending then shorted the source word to reveal the structure of the word class and its phonology. This study brings out the results of the blending process into 4 categories: Complex Clipped Word, Back Clipped Word, The combination of Fore and Back Clipped Word, and Phonemic Overlapping and Clipping. The culture contained in the portmanteau words (the English foods and beverages name) is revealed in the origins of the source words (Borrowing word). They are 13 borrowed words are composed of the name of English foods and beverages. This study is important to develop the fundamental aspects of blending in English food and beverages in Indonesia by looking at the linguistic view and its relation to cultural view.